The use of calcium sulfoaluminate cement to mitigate the alkali silica reaction in mortars. (30th September 2018) - Kleib, J.; Aouad, G.; Louis, G.; Zakhour, M.; Boulos, M.; Rousselet, A.; Bulteel, D.
Highlights: Calcium sulfoaluminate cement has a low alkali content and low pH. An alkali silica reaction test is adapted to study this reaction with both cement. An expansion measurement and microstructural observation were conducted. Calcium sulfoaluminate cement is a good candidate to mitigate the alkali silica reaction. Abstract: The mitigation of the alkali silica reaction in concrete has been the interest of many studies by using low-alkali cement or supplementary cementitious materials. In this paper, calcium sulfoaluminate cement, characterized by its low alkali content and low pH, is used as a mean to reach this goal. Therefore, the main objective is to verify if the composition of a sulfoaluminate cement paste can mitigate the alkali silica reaction compared to that of a Portland cement. The reactive flint aggregate from north of France was used to initiate the alkali silica reaction phenomena with two types of cements: Portland cement CEMI 52.5 N from Holcim, and calcium sulfoaluminate cement Alpenat from Vicat. Alkalis were added by introducing NaOH or NaCl in the mortar mixing solution; six mortars were made. Two references – with Portland or sulfoaluminate cement – without addition of extra amount of alkali, and the four other mortars with either NaOH or NaCl. The results show that, for the reference mortars non expansion/alteration has been detected during the test duration of 140 days. For Portland cement mortar, with same alkali content but coming from two different sources (NaOH or NaCl), the expansion is almost the same. The expansion measurements show that the using of calcium sulfoaluminate cement can mitigate the alkali silica reaction in mortars by reducing its expansion 7 times compared to that of Portland cement mortars. This result was confirmed by the microstructural observations, where the frequency of the alterations – due to the alkali silica reaction – is much less in sulfoaluminate based mortars than the one of the alterations in Portland based mortars.